Inflammatory bowel disease in the Bedouin Arabs of southern Israel: rarity of diagnosis and clinical features. Issue 9 (September 1991) - Odes, H S; Fraser, D; Krugliak, P; Fenyves, D; Fraser, G M; Sperber, A D
Abstract : A prospective epidemiological and clinical study of ulcerative colitis and Crohn's disease was undertaken in the Bedouin Arabs of southern Israel between 1981 and 1990. There were six patients with ulcerative colitis and the prevalence rate in 1990 was calculated to be 9.8/10(5) (95% confidence intervals 3.6-17.4) in the total population, or 6.2/10(5) (0.8-22.5) in men and 13.7/10(5) (3.7-35.0) in women. Two cases of Crohn's disease occurred, both in women; the prevalence rate was 3.2/10(5) (0.4-11.8) in the entire population, and 6.8/10(5) (0.8-17.5) in women. The prevalence rates (age adjusted) in Arabs were significantly lower (p less than 0.01) than the corresponding rates in the local Jewish populations. The Bedouin patients were aged mean (SD) 34.0 (16.4) years at time of diagnosis. The clinical features of both diseases resembled those in the Jewish and other reported populations. It is suggested that the exposure of the Bedouin Arabs to the environmental causative factors of ulcerative colitis and Crohn's disease has hitherto been limited and thereby accounts for the rarity of these diseases in this population.